(untitled) (Research, Society and Development, 2022)
Bidding is the means by which the public administration, whether direct or indirect, acquires goods and services to sustain the public machine. However, there are situations in which this form of acquisition is not advantageous, which is why the law itself, for these cases, made bidding unenforceable, as is the case with the direct hiring of lawyers and law firms that provide a technical service and notorious specialization. Thus, the purpose of this article is the analysis of the discussion about whether or not singularity is proven as an essential requirement for this type of contract, given the introduction into the legal system of the New Law of Bids and Contracts (Law no. 14.133/2021), which suppressed the term "singular nature",’ when compared with the old law (Law no. 8.666/1992), and the change in the statute of the OAB that introduced the singularity and technical service as inherent to the activity of the lawyer. For the conclusion of this work, we used the bibliographic review, the study based on doctrine, scientific articles and brazilian legislation. Therefore, it is concluded that the bidding process is the most isonomic means of contracting by the State, however, the hiring of lawyers presumes its uniqueness and technical service, requiring only to prove its notorious specialization, in order to be able to hire a service of excellence that can satisfy the specific situation.